EXCHANGE ALGORITHM OF BIEXTREMAL SOLUTION TO HOMOGENEOUS ALLOCATION PROBLEM - Rudolph A. Neydorf; Anton V. Filippov; Zafar Khangusein-ogly Yagubov (Advanced Engineering Research, 2011)
An effective algorithm of constructing optimal solutions to homogeneous allocation problems is developed. It is called a biextremal solution algorithm because it permits to find the distribution carrying an extremum to two popular distribution evaluations simultaneously: uniformity of distribution criterion and minimax criterion. The principle of its operation consists in formalizing structure transformation of the core-image matrix derived by Romanovsky’s algorithm with further formalized rearrangement of tasks between their executors. An example of incremental solution to the particular problem is provided.